The “ordinary provisional” in the everyday life of immigrants in São Paulo - Fernandes, Caio; Pachi, Priscilla (Faculdade de Ciências e Letras - Unesp - Araraquara., 2021)
Since 2010 international migration has intensified globally, and Brazil became one of the destinations for many immigrants towards the “south-south” axis. Since then, new migratory routes have brought diversified flows that compose the actual Brazilian migratory scenario. Along with these issues related to the control of people movement and the life management in the cities has arisen. This paper aims to discuss issues concerning the immigrants’ vulnerability in the Metropolitan Region of São Paulo that goes beyond the official migratory policies. Methodologically we use qualitative data provided from participant observation carried out between 2017-2019, semi-structured interviews and quantitative data collected from a documentary analysis by the Federal Police, CONARE, IBGE and Atlas of the São Paulo macro-metropolis were used to compose the reflections presented. In conclusion, this paper argues that immigrants’’ everyday life is composed by a transversal “ordinary provisional” in relation to the city’s dynamics.